Travellers in Time - Wallace, Saro, author.
1 online resource (560 pages)
Keywords: "Travellers in Time re-evaluates the extent to which the earliest Mediterranean civilizations were affected by population movement. It revisits the traditional notion of movement as straightforwardly transformative as well as the processual, systemic models that replaced this view, arguing that new scholarship too often pays limited attention to the specific encounters, experiences and agents involved in travel. By assessing a broad range of recent archaeological and ancient textual data from the Aegean and central and east Mediterranean via five comprehensive studies, this book makes a compelling case for rethinking issues such as identity, agency, materiality and experience through an understanding of movement as transformative.This innovative and timely study will be of interest to advanced undergraduates, post-graduate students and scholars in the fields of history and Classical archaeology, as well as anyone interested in ancient Aegean and Mediterranean culture."--Provided by publisher.